Interrelation between morphology of foot and body build - Łuba, Ryszard (Anthropological Review, 1977)
The aim of this paper is to analyse how physiological capacity of foot adapts itself to static and dynamic stresses. The method applied was the analysis of relations of suitably selected dimensions and proportions of foot to general characteristics of body build. The material comprises measurements of 402 females aged 19 - 35 years, 648 females aged 36 - 60 years, 366 males aged 19 - 35 years and 391 males aged 36 - 60 years. In the tables are given mean values, standard deviations and correlation coefficients of each character with: foot length (rax), body weight (rbx), body height (rcx). weight to height index (rdx) and index of stress exerted on foot (rex). Numbers denoting characters in the table are the same as on fig. 1 (numbers 1-9), 10 denotes body weight, 11 — body height, 12 — index calculated as (4:1)X100, 13 — index (6:1)X100, 14 — index (7:1)X100, 15 — index (4:8)X100, 16 — index (6:7)X100, 17 — index (5:6)X100, 18 — index (5:9)X100, 19 — index (10:11)X100 — weight to height index, 20 — index (10:1) — index of stress exerted on foot, 21 — index (2:6)X100, 22 — index (3:6)X100.